Equitable Shifts in Youth Resilience? Distinguishing Normative Changes and Pandemic Effects on Academic Self-Efficacy and Cognitive Reappraisal - Repo, Juuso; Herkama, Sanna; Salmivalli, Christina (AMER PSYCHOLOGICAL ASSOC, 2025)
This preregistered longitudinal study examined the long-term effects of the COVID-19 pandemic on academic self-efficacy and cognitive reappraisal in early adolescence. It followed and compared two cohorts over 4 years: one prepandemic (11-14 years, 2016-2019) and one during the pandemic (2019-2022). The study analyzed annual well-being surveys merged with school enrolment data from South Australian public schools (N = 28,307, 49% female). Employing latent growth modeling and a novel cohort comparison design, the study addressed a major limitation in pandemic studies: It separated pandemic effects from normative developmental changes. Results indicate that the pandemic cohort largely followed typical, yet declining, developmental trajectories, showing resilience at a population level. Unexpectedly, the examination of multiple covariates (i.e., gender, socioeconomic status, non-English background, anxiety, peer belonging, teacher support) showed that preexisting vulnerabilities did not predict adverse pandemic effects. This research underscores the value of longitudinal data infrastructures and the importance of understanding normative youth development and resilience research in discerning the effects of pandemics or other widespread crises.